2013
DOI: 10.1177/039463201302600416
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Assessment of Salivary Gland Neoplasms with Fine Needle Aspiration Cytology and Echography: A Retrospective Analysis of 357 Cases

Abstract: Fine-needle aspiration cytology (FNAC) is a minimally invasive procedure usually well tolerated, easy to perform, quick, cheap and easy to repeat in case of doubts or non-diagnostic results. Echography is also a fast, cheap and non-invasive tool; however, the role of FNAC and echography in the diagnosis of salivary gland pathology is not universally recognised. Three hundred and fifty-seven patients with a cytological diagnosis at FNAC, and 247 of these who were also studied with echography, were enrolled for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…The sensitivity of FNA, as mentioned in different previous studies, varies from 54% to 98% with high specificity values of 88% to 99% for separating benign lesions from malignant lesions. 8,9 Similarly, in the current study, the sensitivity was 76.3% and the specificity was 92.6%.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…The sensitivity of FNA, as mentioned in different previous studies, varies from 54% to 98% with high specificity values of 88% to 99% for separating benign lesions from malignant lesions. 8,9 Similarly, in the current study, the sensitivity was 76.3% and the specificity was 92.6%.…”
Section: Resultssupporting
confidence: 74%
“…8,9 Similarly, in the current study, the sensitivity was 76.3% and the specificity was 92.6%. 8,9 Similarly, in the current study, the sensitivity was 76.3% and the specificity was 92.6%.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…(7) On the other hand, Pastore et al found a sensitivity and specificity of 83% and 93% respectively to detect malignancy. (8) Fakhry et al evaluated 249 parotid tumours, out of which 75% were benign and 25% were malignant. (9) The sensitivity and specificity to detect malignancy was assessed to be 80% and 89.5% respectively.…”
Section: Discussionmentioning
confidence: 99%